KAJIAN HUKUM TERHADAP PERKEMBANGAN HUKUM KEPAILITAN DI INDONESIA (Faculty of Law, University of Palembang, 2024)
Bankruptcy law is one area of bussines law that continues to experience very rapid development today, especially in term of legal practice. Currently, many developments have occurred in the field of bankruptcy law, including regarding the settlement of debtor debt, the position of separatist creditors, the position of worker wages in bankruptcy, the position of tax debt in bankruptcy, as well as the position of curator fees and bankruptcy costs, all of which must take priority in payment. However, bankruptcy law itself does not fully accommodate these matters.